Structural Condition Assessment of the Herringbone Middle Pylon of the Taizhou Bridge Using SHM Strain Data. (7th September 2017) - Ding, Huaping; Shen, Qinghong; Du, Sidan
Abstract : Taizhou Bridge is the world's first kilometer-scale three-pylon suspension bridge. To minimize the impacts on navigation, a longitudinal herringbone steel pylon was adopted in the middle of the bridge without additional piers. This structure is unique, and little research has focused on its structural condition assessment. In this paper, eighty fiber Bragg grating strain sensors were deployed along the height of the steel tower to collect strain data about the key components and to monitor the pylon's structural condition. Because temperature-induced strain contributes little to the stress in the pylon, the empirical mode decomposition method was proposed to remove the noise and the temperature-induced strain, leaving the dynamic strain response. The frequency characteristics were obtained from both the dynamic strain and the raw strain, and they show good agreement. A statistical analysis was adopted assuming that the extracted dynamic stress peaks and valleys were normally distributed. The expected maximum values from the statistical analysis were compared with the measured maximum values at different heights, and they agree well with each other. The maximum compression and tension of the key segments of the middle tower exhibited considerable redundancy, which indicates that the middle pylon is in good condition.